Centralization or decentralization? A review on the effects of information and communication technology on urban spatial structure. (August 2018) - Dadashpoor, Hashem; Yousefi, Zahed
Abstract: Information and communication technology (ICT) can play an important role in shaping and modifying the urban spatial structure through its effects on the elements and factors that shape this structure. There are many studies that have focused on these effects and studied the impacts of ICT on urban elements and functions. The results of most of these studies are based on arguments about the impacts of these technologies on decentralization or centralization trends in urban spatial structure. In this study, we attempt to categorize the findings of the related studies through a literature review. Although ICT includes conventional communication media such as radio, television, and landlines, here we only focused on new technologies, especially the Internet and mobile phone. For this aim, related studies were searched using wide range of keywords in four scientific information databases for researches published in English and the search period was limited according to the nature of the subject from 1990 to 2017. Subsequently, with the study of the abstracts and the findings of the studies, at last, 80 articles related to the topic were selected for literature review. The result of this review showed that theoretical viewpoints on spatial effects of ICT on urban spatial structure can be categorized into four approaches: A) centralization effects; B) decentralization effects; C) dual effects (both centralization and decentralization); and D) low impact or no effects. The results also indicate that most studies have been focused on the decentralization (42%) and dual effects (33%) impacts, some emphasize on centralization effects (16%), and few studies have also concluded that ICT does not have any effect on the spatial structure of cities or its effects are negligible (9%). Generally, it can be concluded that majority of scholars have consensus that ICT can affect urban spatial structure; what is controversial is only the way of these effects and consequences. Therefore, a proper understanding of the relationship between ICT and the urban spatial structure is essential for urban planners, professionals, researchers and managers. Highlights: Information and communication technology (ICT) can play an important role in shaping the urban spatial structure. This article attempts to answer the question whether ICT has decentralized traditional concentrated structure of cities? Majority of scholars have consensus that ICT can affect urban spatial structure. A proper understanding of the relationship between ICT and the urban spatial structure is essential for urban planners.